Improving Outcomes for Shell and Shucking By-Products in Australian Abalone Fisheries – A Supply Chain Perspective - Loo, Lynne Xin Hui (Curtin University, 2023)
This research responds to global targets to halve food waste by 2030 and the Australian abalone industry’s need to maximise returns on catch by utilising shucking by-products. Both these exigencies are addressed by quantifying food waste and understanding its drivers. Analysis revealed that Australia’s wild-harvest abalone industry faces several barriers to recovering and valorising commercially-viable volumes of waste arising from heavily-regulated supply and vast geographical distances. Supply chain collaboration is necessary to overcome these challenges.